Optimizing exercise outcomes: The efficacy of resistance training using conventional vs. novel movement arcs - Richards, J. A.; Dawson, T. A. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this study was to examine the effect of using multidirectional movement arcs in a resistance training program for the shoulder. It was hypothesized that multidirectional exercises performed against resistance would result in a greater positive adaptation of the muscle tissue than conventional movement patterns commonly used in strength training. Fourteen female athletes were initially assessed using a 1× repetition maximum (1×RM) test for shoulder flexion and shoulder abduction (dominant and nondominant arm). After randomization into 2 groups, subjects engaged in different strength training programs against Thera-Band resistance for 6 weeks. Follow-up testing was then completed. Group A was assigned a strength training program that used conventional curvilinear movement arcs. Group B completed resistance training that comprised multidirectional exercises. Both the conventional and novel strength training programs induced improvements in the 1× RM test (p < 0.01). There was a trend toward greater improvements in the nonconventional training group, but this was statistically insignificant. This suggests that varying the axial or torsional loading of muscle fibers during strength training may confer further benefit to conventional methods of training variation. Consequently, further studies are indicated to investigate if resistance training that incorporates multidirectional movement arcs is more effective than those used in conventional strength training programs. This may have implications on the design of future training programs that aim to optimize strength gains.